Temporal shifts in the distribution of murine rodent body size classes at Liang Bua (Flores, Indonesia) reveal new insights into the paleoecology of Homo floresiensis and associated fauna. Issue 130 (May 2019) - Veatch, E. Grace; Tocheri, Matthew W.; Sutikna, Thomas; McGrath, Kate; Wahyu Saptomo, E.; Jatmiko,; Helgen, Kristofer M.
Abstract: Liang Bua, the type locality of Homo floresiensis, is a limestone cave located in the western part of the Indonesian island of Flores. The relatively continuous stratigraphic sequence of the site spans the past ∼190 kyr and contains ∼275, 000 taxonomically identifiable vertebrate skeletal elements, ∼80% of which belong to murine rodent taxa (i.e., rats). Six described genera are present at Liang Bua ( Papagomys, Spelaeomys, Hooijeromys, Komodomys, Paulamys, and Rattus ), one of which, Hooijeromys, is newly recorded in the site deposits, being previously known only from Early to Middle Pleistocene sites in central Flores. Measurements of the proximal femur ( n  = 10, 212) and distal humerus ( n  = 1186) indicate five murine body size classes ranging from small (mouse-sized) to giant (common rabbit-sized) are present. The proportions of these five classes across successive stratigraphic units reveal two major changes in murine body size distribution due to significant shifts in the abundances of more open habitat-adapted medium-sized murines versus more closed habitat-adapted smaller-sized ones. One of these changes suggests a modest increase in available open habitats occurred ∼3 ka, likely the result of anthropogenic changes to the landscape related to farming by modern human populations. The other and more significant change occurred ∼60 ka suggesting a rapid shift from more open habitats to more closed conditions at this time. The abrupt reduction of medium-sized murines, along with the disappearance of H. floresiensis, Stegodon florensis insularis (an extinct proboscidean), Varanus komodoensis (Komodo dragon), Leptoptilos robustus (giant marabou stork), and Trigonoceps sp. (vulture) at Liang Bua ∼60–50 ka, is likely the consequence of these animals preferring and tracking more open habitats to elsewhere on the island. If correct, then the precise timing and nature of the extinction of H. floresiensis and its contemporaries must await new discoveries at Liang Bua or other as yet unexcavated sites on Flores.